The Effect of Breastfeeding Education Using Leaflet Media on the Knowledge and Attitudes of Pregnant Women - Jannung, Orpa; Nailufar, Farida; Satriani, Satriani; Wahyutri, Endah (Journal of Health and Nutrition Research, 2024)
Breast milk (BM) is one of the most important nutrients for baby needs. This is the best baby food for the perfection of growth and development. Increasing the knowledge and attitude of mothers is considered necessary because it contributes to parenting for their children. This research aims to determine the effect of breastfeeding education using leaflet media on the knowledge and attitudes of pregnant women. The research is a quasi-experiment with a pre-test and post-test with a control group research design conducted in March – April 2023 in the working area of the South Sangatta Health Center, East Kutai Regency, East Kalimantan, Indonesia. A total of 32 samples were involved in random sampling by taking into account inclusion and exclusion criteria. The data is analyzed with the Paired-Sample T-test. The research shows the influence of exclusive breastfeeding education using leaflet media on the knowledge of pregnant women (p = 0.000), and the influence of exclusive breastfeeding education using non-leaflet media on the knowledge of pregnant women (p = 0.006). There is an influence of exclusive breastfeeding education using leaflet media on the attitude of pregnant women (p = 0.000), and the influence of exclusive breastfeeding education using non-leaflet media on the attitude of pregnant women (p = 0.006). Education using leaflets is much more effective than non-leaflet education. This finding is empirical evidence that nutrition education in the form of media is encouraged to welcome changes in public perception